2007
DOI: 10.4103/0028-3886.30432
|View full text |Cite
|
Sign up to set email alerts
|

An interesting case report of Morvan′s syndrome from the Indian subcontinent

Abstract: The French physician Augustine Marie Morvan first used the term 'la choriotae fibrillare' to describe a syndrome characterized by peripheral nerve hyperexcitability, dysautonomia, insomnia and fluctuating delirium. There are no published reports of the condition from the Indian subcontinent. We report the first such case from the region. Our patient, a 24-year-old male, presented with easy fatigability and stiffness in both the calves for 18 months; continuous twitching of muscles of all four limbs and jaw for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 4 publications
1
9
0
Order By: Relevance
“…Plasma exchange was proposed initially as the mainstay of treatment for Mos [12]. Steroids have also proved beneficial [5,10] while IVIG did not show efficacy in two other cases. Spontaneous recovery has also been reported [3].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Plasma exchange was proposed initially as the mainstay of treatment for Mos [12]. Steroids have also proved beneficial [5,10] while IVIG did not show efficacy in two other cases. Spontaneous recovery has also been reported [3].…”
Section: Discussionmentioning
confidence: 96%
“…The diagnosis was supported by the presence of VGKCcomplex antibodies in serum which were detected at high titres (1416 pM/L) as well as by immunohistochemistry and by cell binding assay. There are very few MoS cases described in the English literature [4,3,5,6,[10][11][12][13][14], although 29 additional cases have been collected (Irani SR, Vincent A in preparation). In a recent study by Irani et al (2010) [7], of 96 patients positive for VGKC antibodies, only 5 were identified as having MoS, illustrating the rarity of the syndrome.…”
Section: Discussionmentioning
confidence: 96%
“…It is thought to be autoimmune in most cases. The syndrome is occasionally noted to be a paraneoplastic manifestation of tumors such as a thymoma or small‐cell carcinoma and is seen in association with autoimmune thyroiditis and myasthenia gravis 2 . It is referred to as Isaac's syndrome when the autonomic or central symptoms are lacking 3 …”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous improvements can occur in some patients, especially if an underlying condition is found that is amenable to treatment. Newer modalities including positron emission tomography, single photon emission computed tomography, and functional MRI, along with examination of antibody levels in the blood, are likely to lead to better understanding of the syndrome and its relationship with other disorders with continuous muscle fiber activity 2 …”
Section: Discussionmentioning
confidence: 99%
“…Various European and subsequently, Asian authors have reported individual case reports or case series of Morvan's syndrome. [12] The pathogenesis of Morvan's syndrome was earlier speculated to be due to exposure to toxins, particularly heavy metals and/or presence of autoantibodies. The association of the syndrome with malignancies mostly thymoma as a paraneoplastic manifestation was subsequently recognized.…”
mentioning
confidence: 99%